The physicochemical and flotation characteristics of fine sphalerite activator - Dulatbek Turysbekov; Nessipbay Tussupbayev; Bagdaulet Kenzhaliev; Muhammad Noorazlan Abd Azis; Sabira Narbekova; Nazira Samenova; Larissa Semushkina (Discover Applied Sciences)
Abstract Technological challenges are encountered in the flotation recovery of zinc minerals from polymetallic ores. Typically, copper-lead-zinc ores are processed through a preliminary bulk flotation of all sulfide minerals, followed by separation of the bulk concentrate. From this bulk concentrate, a copper-lead concentrate is obtained, during which zinc and iron minerals are depressed. The subsequent task involves selectively recovering a zinc concentrate by maintaining the depression of iron minerals. That is, the zinc minerals remain in a depressed state and must be activated to become flotable. Copper sulfate is traditionally used as an activator for sphalerite; however, it is a significant source of sulfate ions in wastewater, posing environmental concerns. Therefore, the search for alternative sphalerite activators with reduced environmental impact is a relevant and pressing issue. Copper sulfide is considered as a potential alternative activator. The activating effect of copper sulfide was tested on a monomineralic sphalerite fraction with a particle size of 98.11% below 40 μm, depending on solution pH and activator dosage. The highest degree of sphalerite activation was observed at a pH range of 6–8. The optimal dosage of the conventional activator, copper sulfate, was determined to be 80 mg/dm³, whereas the optimal dosage of copper sulfide was 40 mg/dm³. Results from monomineralic flotation tests demonstrated that the recovery of sphalerite increased by 5–7% when copper sulfide was used, compared to copper sulfate.